Different Swine Production Systems Can Shape Slurry Resistome at Mechanism and Class Levels Based on Swine Manure Evaluation - Beltrame, Lucas Cafferati; Zamparette, Caetana Paes; Feltrin, Clarissa; da Cunha, Caroline Ribeiro; Coltro, Elisa Pires; Athayde, Gabriel Saldanha da Silva; Filho, Vilmar Benetti; Tápparo, Deisi Cristina; Monteiro, Jamir; Kich, Jalusa Deon; Palmeiro, Jussara Kasuko; Wagner, Glauber; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Antimicrobial resistance is a major threat to public health. Antimicrobial use in animal husbandry is a major concern since it can favor an increase in antimicrobial resistance among farms. Herein, we aim to better understand and characterize the main resistome profiles in microbial communities found in pig farms. Sampling of swine manure was performed in different swine farms, located in the mesoregion of Western Santa Catarina state - Brazil, a pole of swine products production of worldwide importance. Samples were divided into three groups: farms with the opened regimen and no usage of antimicrobials (F1; n = 10), farms with the closed regimen and usage of antimicrobials (F2; n = 16), and farms with the closed regimen and no usage of antimicrobials (F3; n = 2). The metagenomic evaluation was performed to obtain and identify genetic elements related to antimicrobial resistance using nanopore sequencing. We used ResistoXplorer software to perform composition, alpha and beta-diversity, and clustering analysis. In addition, PCR reactions were performed to detect the resistance genes blaCTX-M-1, blaCTX-M-2, blaCTX-M-9, blaKPC, blaNDM, blaSHV, blaTEM, mcr-1, mcr-2, mcr-3, mcr-4 and mcr-5. Our findings based on the identification of resistance genes at mechanism level showed a prevalence of alteration of drug target (72.3%) profile, followed by drug inactivation (17.5%) and drug efflux (10.1%). We identified predominantly aminoglycosides (45.3%), tetracyclines (15.9%) and multiclass (11,2%) resistance genes. PCoA analysis indicates differences between F1 and F2 profiles. F2 samples showed increased diversity when compared to the F1 group. In general, our findings reinforce that many factors on the practices of animal husbandry are involved in the resistome profile at mechanism and class level. Further studies to better understand microbiome and mobilome aspects of these elements are necessary to elucidate transmission pathways between different bacteria and environments.